Microbiological risk assessment of fresh water aquaculture fish: From farm to table - Abu Bakar, Ibrahim; Ayob, Mohdkhan; Abdullah Sani, Norrakiah (American-Eurasian Network for Scientific Information, 2014)
The qualitative microbiological risk assessments of fresh water aquaculture fish from farms, markets and food premises have been carried out in six main aquaculture fish production districts in Malaysia. Three species of fish were involved in this study [red tilapia (Oreachromis sp. red hybrids), keli (Clarias spp.) and patin (Pangasius sutchii)]. About 240 fresh fish (90 red tilapia, 60 keli and 90 patin) were randomly collected direct from their farms (earth ponds, floating net cages and examining pools). Another 240 fish with the same ratio as farm fish samples were also randomly collected from various markets (wet markets, local markets called ‘pasar tani’ and night markets). The same number of samples with the same ratio of ready-to-eat fish from food premises (restaurants, food stalls and night market food stalls) was also collected. Three indicator microorganisms (TPC, coliform and faecal coliform) as well as seven pathogenic organisms (E. coli, S. aureus, Salmonella spp., Campylobacter spp., B. cereus, Aeromonas spp. and Pseudomonas spp.) were analyzed. The results showed that there were intermediate microbiological risk in farm and market fish samples and low microbiological risk in ready to eat fish samples.